Provision of Data Processing Services (MENA Report, 2013)
notice number in oj : 2013 / s 73-122141 of 13.4.2013 vi.2) additional information: vi.3 ) rechtsbehelfsverfahren/nachprufungsverfahrenvi.3.1 ) body responsible for rechtsbehelfs-/nachprufungsverfahrenvi.3.2 ) lodging of rechtsbehelfenvi.3.3 ) service from which information about the lodging of appeals erteiltvi.4 ) date of dispatch of this notice: (c) 2013 Al Bawaba (Albawaba.com)